A Typology of Attribution Leadership Research - McElroy, James C. (Academy of Management Review, 1982)
A typology of leadership research utilizing an attributional paradigm is presented. Studies are typed according to three pertinent questions: (1) What is to be studied? (2) Whom do you ask? and (3) What is the purpose of the research? The typology reveals that most of the research using the attribution paradigm is descriptive rather than prescriptive. Moreover, there is a serious lack of prescriptive-process research. Future research matching superior and subordinate attributional tendencies is suggested.